The Music of the Troubadours - Aubrey, Elizabeth (Bloomington, IN Indiana University Press, 1996)
[I]nvaluable for musicologists and troubadour scholars interested in knowing about the 'whole song', and it also provides an excellent introduction to troubadour music for the historian, philologist or, indeed, anyone with a passing interest." David Cashman, Parergon"It is a down-to-earth treatment of the discernible facts, ordered according to the type of evidence that survives. It is a book to sober up the discipline." Daniel Leech-Wilkinson,Times Literary Supplement[A] welcome guide for the growing number of performers wishing to recreate these magical treaures from the medieval Midi." Donna Mayer-Martin, NotesThe Music of the Troubadours is the first comprehensive critical study of the 315 extant melodies of the troubadours of Occitania. It begins with an overview of their social and political milieu in the 12th and 13th centuries, then provides brief biographies of the 42 troubadours whose music survives. The four manuscripts that transmit this music are described in detail, with attention to their genesis in the overlapping roles of composers, singers, and scribes.To examine the poetic traditions within which the troubadours composed, Aubrey discusses genre, versification, and poetic style. An in-depth analysis of melodic forms and styles reveals traits of individual composers and offers a broad view of the chronological development of the music of the troubadours. Performance practice issues such as rhythm, ornamentation, chromatic inflections, and the use of instruments are explored, thus helping modern performers to bring these ancient treasures to life again.
Keywords: Middle Ages (500-1400); Troubadour; Music history; France; Occitanie (France)